Structural Modifications of Nile Red Carbon Monoxide Fluorescent Probe: Sensing Mechanism and Applications - Madea, Dominik; Martínek, Marek; Muchová, Lucie; Váňa, Jiří; Vítek, Libor; Klán, Petr (American Chemical Society, 2020)
Carbon monoxide (CO) is a cell-signaling molecule (gasotransmitter) produced endogenously by oxidative catabolism of heme, and the understanding of its spatial and temporal sensing at the cellular level is still an open challenge. Synthesis, optical properties, and study of the sensing mechanism of Nile red Pd-based CO chemosensors, structurally modified by core and bridge substituents, in methanol and aqueous solutions are reported in this work. The sensing fluorescence "off-on" response of palladacycle-based sensors possessing low-background fluorescence arises from their reaction with CO to release the corresponding highly fluorescent Nile red derivatives in the final step. Our mechanistic study showed that electron-withdrawing and electron-donating core substituents affect the rate-determining step of the reaction. More importantly, the substituents were found to have a substantial effect on the Nile red sensor fluorescence quantum yields, hereby defining the sensing detection limit. The highest overall fluorescence and sensing rate enhancements were found for a 2-hydroxy palladacycle derivative, which was used in subsequent biological studies on mouse hepatoma cells as it easily crosses the cell membrane and qualitatively traces the localization of CO within the intracellular compartment with the linear quantitative response to increasing CO concentrations.
Fluorescenční sondy pro detekci CO založené na modifikované nilské červeni: mechanismus účinku a aplikace
Keywords: Nile red; carbon monooxide; fluorescent Probe; chemosensors; nilská červeň; oxid uhelnatý; fluorescenční sonda; chemosenzory